Effects of Adding Coal Ash vs Rice Husk Ash on Compressive Strength of Mortar - Sudirman Sudirman (Lembaga Pengembangan Kinerja Dosen, 2024)
Coal is widely used as an energy source in several industries, especially for power plants (PLN), but on the other hand this causes waste problems or environmental impacts. Several studies have been carried out to utilize coal ash waste (fly ash) as an additional material [or as a partial substitution material] in making mortar. This research aims to determine the effect of adding coal ash and rice husk ash with variations of 5%, 10% and 15% of cement weight respectively (at ages 3 days, 7 days, 14 days, 21 days and 28 days). on the 'compressive strength' and 'absorption capacity' values of the mortar. This research uses quantitative methods through a series of experiments on 60 samples or test objects with the addition of coal ash (fly ash) and rice husk ash in the mortar mixture with reference to the Indonesian National Standard (SNI 03-6825-2002). Next, a series of tests were carried out at the age of 3 days, 7 days, 14 days, 21 days and 28 days to calculate the ' strong ' value. press' and ' power absorb' mortar. The research results showed that with the addition of coal ash and rice husk ash, the mortar experienced a significant increase in 'compressive strength' when compared to ordinary mortar, the strength of the mortar reached the optimum level at a variation of 15% addition of the cement weight, reaching 240.96 kg /cm 2 . Meanwhile, with the addition of husk ash in the same variation, the compressive strength of the mortar reached 204.82 kg/cm 2 .